Pengembangan Model Masker U Can See Dalam Deteksi Dini Kegawatdaruratan Maternal Di Puskesmas Cibadak Tahun 2021 - Anis Ervina; Pipin Agis Susanti; Siti Shela Nur Sholehah; Chysera Kusuma Wijaya; Siti Sulati (Akademi Kebidanan La Tansa Mashiro, 2022)
During the pandemic, everyone is required to wear a mask inacordance with the health procedures issued by the ministry of health in 2019 that transmission of COVID-19 accurs through droplets that can infect humans by entering droplets containing the sars cov 2 virus into the body through the mouth and eyes. To prevent the spread of COVID-19, the public is required to wear a mask, but this has an impact on the lips being convered by a mask, making it difficult to see the signs of an emergency that can be seen from the condition of the lips. Therefore in early detection of emergencies in the lip area by looking at the color of the lipss that can determine emergencies in pregnant women in labor and postpartum, especially those who experience hypoxia. This research method is a description of the effectiveness of the use of u can see masks in early emergency detection of pregnant women giving birth and this study aims to detect early emergencies through u can see masks.